2(2z-5)=3(z+5)+z

Simple and best practice solution for 2(2z-5)=3(z+5)+z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2z-5)=3(z+5)+z equation:


Simplifying
2(2z + -5) = 3(z + 5) + z

Reorder the terms:
2(-5 + 2z) = 3(z + 5) + z
(-5 * 2 + 2z * 2) = 3(z + 5) + z
(-10 + 4z) = 3(z + 5) + z

Reorder the terms:
-10 + 4z = 3(5 + z) + z
-10 + 4z = (5 * 3 + z * 3) + z
-10 + 4z = (15 + 3z) + z

Combine like terms: 3z + z = 4z
-10 + 4z = 15 + 4z

Add '-4z' to each side of the equation.
-10 + 4z + -4z = 15 + 4z + -4z

Combine like terms: 4z + -4z = 0
-10 + 0 = 15 + 4z + -4z
-10 = 15 + 4z + -4z

Combine like terms: 4z + -4z = 0
-10 = 15 + 0
-10 = 15

Solving
-10 = 15

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -18+c=18+10c-13c | | -45=-2n+3 | | -20+4s-18=18-10s | | 4n=7n+2 | | 2x^2+10=8x | | 5x+2x=7x-6 | | C^2=9+16 | | -9+5x+6x=8 | | X+7-7x=-47 | | 2(10)-5y=8 | | -12+6n=15+4n+13 | | 8=-d+17 | | 7(4-3x)=2(8x-9) | | 7-14p= | | 17-6f=-5f-3 | | r+3.3=8 | | 8x-10=-8+3x | | -4=-8p+11+9p | | 6(-4x-1)=-150 | | -10-4x+8=10x-15 | | 14b+18=7+15b | | 4p+4=5p+7 | | -2-4x=6x+28 | | 3a+2b=5c | | 0.50x+13=9 | | 3x-48y=12 | | -17p-4=-16p | | 9(z-1)=16 | | 15-15x-6-45x+25-25x=0 | | 0.03(7t-9)=0.21(t-5)+0.78 | | 13+3g=2g | | 9=v-7 |

Equations solver categories